The yeild ratio of the isomeric pair 107m.107 Hg formed by 197 Au (d,2n) 107 Hg reaction - Abecasis, S.; Jorge Nassif, Sonia (Pergamon Press, 1961)
Fil: Abecasis, S. Comisión Nacional de Energía Atómica; Argentina